Prevalence of occupational stress using salivary alpha-amylase and its associated factors among oil palm harvesters at Carey Island, Selangor, Malaysia - Mohd Nasir, Nur Sabrina (2016)
Methodology: This cross-sectional study was conducted for three weeks at six divisions from two oil palm plantation at Carey Island, Selangor. One hundred and nine oil palm harvesters were recruited. Questionnaire was used to determine socio-demographic and occupation background. Psychological distress was determined using the General Health Questionnaire-12 (GHQ-12). Kestrel Heat Stress Tracker 4400 was used to measure wet bulb globe temperature outdoor (WBGToutdoor) to determine heat stress exposure. Postural analysis was assessed using Rapid Upper Limb Assessment (RULA) method and Borg CR-10 scale was used to determine exerted force during harvesting work task. Salivary alpha-amylase assay kit was used to analyse the salivary alpha-amylase levels which is used as an indicator of occupational stress. Results: The response rate was 100%. The Cronbach’s alpha coefficient for Indonesian translated version of GHQ-12 is acceptable (α=0.70). Ninety five percent of the respondents were Indonesian aged between 19 to 46 years old. The prevalence of occupational stress among respondents was 77.0% based on high level of salivary alphaamylase activity at post harvesting. Thirty six percent of respondent experienced a psychological distress state and 45.9% exposed to heat stress during harvesting work task. Postural analysis classified 62.4% of the respondents in Action Level 4 based on RULA method. Maximum of three times cutting the subtending the oil palm frond reported by the respondents. Ninety two percent of the respondents applied high force (≥ %50 MVC) during cutting the stalk of fresh fruit bunch. Result from Chi-square test showed that the stressors significantly associated with occupational stress were psychological distress (　2=5.524, p=0.019), heat stress exposure (　2=31.851, p<0.001), working posture (　2=4.289, p=0.038), force exertion on cutting oil palm frond once (　2=0.479, p=0.489), force exertion on cutting oil palm frond twice (　2=0.202, p=0.653), force exertion on cutting oil palm frond for three times (　2=9.341, p=0.002). Further analysis using simple and multiple linear regression, showed that predictive stressors for occupational stress were WBGToutdoor (ß=0.747, p<0.001) and cutting oil palm frond for three times (ß=-0.175, p<0.05). Conclusion: The prevalence of occupational stress in this study is 77.1%. The prevalence of psychological distress in this study was low (35.8%) but it was significantly associated with occupational stress. Fifty percent of the respondents exposed to heat stress while performing the harvesting task and found to be a contributing factor for occupational stress among oil palm harvesters. The movement and alignment of body posture while performing the harvesting work task is significantly associated with occupational stress. Sixty three percent of the workers are performing the harvesting task in awkward position. Most of the workers experienced stress when they exerted force to cut the subtending oil palm frond for three times. On the contrary, all the workers were pleasant to cut the fresh fruit bunch though many of them exerted the high force to cut the stalk of fresh fruit bunch. It can be concluded that occupational stress among oil palm harvesters is influenced by exposure of excessive heat, awkward working posture, psychological distress and cutting the subtending oil palm frond for three times. The most influencing factors for occupational stress among oil palm harvesters are heat stress exposure and force exertion applied for three times to cut the subtending oil palm frond.